Freedom Learning in University (MBKM): Strengthening Social Studies Curriculum Through Critical Pedagogy - Adhitya Wulanata Chrismastianto, Imanuel; Kerti Nitiasih, Putu; Nanci Riastin, Putu (KnE Social Sciences, 2024)
The emergence of society 5.0 era opens opportunities as well as challenges that are increasingly complex for the education world existence and progress with information and communication technology (ICT) support in learning process which is expected to be able to produce students who are adaptive to social changes around them. A lack of relevant curriculum regarding access to learning and technology is also still a challenge for the education world. The education system and social studies curriculum in Indonesia must improve to be able to adapt to science and technology development in this society 5.0 era through a critical pedagogical theory approach. The paper aims to contribute visible ideas on strengthening the social studies curriculum through critical pedagogy in the MBKM context. The research method used is qualitative with a literature review that is relevant to the social studies curriculum through critical pedagogy in the MBKM context. The analysis results show that strengthening the social studies curriculum through critical pedagogy in the MBKM context is by implementing the significant learning models and providing space for developing student competencies. Keywords: critical pedagogy, freedom learning, MBKM, social studies curriculum